2018
DOI: 10.1136/bmjopen-2017-020007
|View full text |Cite
|
Sign up to set email alerts
|

Empathy, burn-out and the use of gut feeling: a cross-sectional survey of Danish general practitioners

Abstract: ObjectiveResearch has suggested that physicians’ gut feelings are associated with parents’ concerns for the well-being of their children. Gut feeling is particularly important in diagnosis of serious low-incidence diseases in primary care. Therefore, the aim of this study was to examine whether empathy, that is, the ability to understand what another person is experiencing, relates to general practitioners’ (GPs) use of gut feelings. Since empathy is associated with burn-out, we also examined whether the hypot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 34 publications
(56 reference statements)
1
18
0
3
Order By: Relevance
“…Thus, in one study of 3890 children presenting in primary care, parental concern strongly influenced the GPs’ GF about serious infections in the children 9. In line with this, we have found that GPs who score high on empathy and, hypothetically are more sensitive to patients’ concerns, reported to use GF in their daily practice to a higher degree than GPs who scored low 10. It is not known whether high empathy is associated with higher use of GF in cancer diagnosis.…”
Section: Introductionsupporting
confidence: 70%
“…Thus, in one study of 3890 children presenting in primary care, parental concern strongly influenced the GPs’ GF about serious infections in the children 9. In line with this, we have found that GPs who score high on empathy and, hypothetically are more sensitive to patients’ concerns, reported to use GF in their daily practice to a higher degree than GPs who scored low 10. It is not known whether high empathy is associated with higher use of GF in cancer diagnosis.…”
Section: Introductionsupporting
confidence: 70%
“…While the overall prevalence of burnout was estimated to range from 2.6% to 69.9%, emotional exhaustion (EE) was observed in 8.7–63.2%, depersonalisation (DP) in 8.5–52% and low personal accomplishment (PA) in 4.4–73.3%. 8–34 Burnout prevalence varies among different subgroups of physicians (eg, general practitioners, anaesthetists, senior doctors and dentists).…”
Section: Introductionmentioning
confidence: 99%
“…Our group has undertaken several studies to analyze the impact of burnout and empathy among general practitioners (GPs) and nurses on different aspects of primary care practice (Yuguero et al, 2017a). Moreover, this relation between empathy and burnout has also been described in other countries (Sun et al, 2017;Pedersen et al, 2018) and in other health care groups among emergency professionals (Yuguero et al, 2017a), psychiatrists (Bentley et al, 2018) and intensive care professionals (van Mol et al, 2015). In all cases, high empathy has been described as a contributing factor of burnout prevention.…”
Section: Introductionmentioning
confidence: 99%